Productivity improvement for visual inspection using lean concept a case study at front of line process - Augustine, Noel Francisco (2016)
Nowadays,semiconductor manufacturing companies aim for higher productivity with short lead time that will maximize the profit to the organization for their survival. This project is conducted at Infineon Technologies(M)Sdn.Bhd. especially at Front of Line area that focusing on quality performance of visual inspection for die bond and wire bond processes. There are redundant quality visual inspection activities between Production operators and Process Control operators.Here, the production operators whom operate the machines while Process Control operators whom conducting quality surveillance checks perform similar quality visual inspection. Furthermore, there is inconsistent duration of visual inspection activities although the standard work instruction has been provided. Therefore, the aim of the project is to improve the productivity of visual inspection process through elimination of non-value activities at Dpak package Front of Line process by 50%. There are three objectives defined for this project; (i) to identify the NV A and NVA but necessary activities using time study, (ii) to determine root cause of NVA and NVA but necessary and perform simulation with proposed action and (iii) to validate the proposed solutions through implementation of actions for improvement. Time study and brainstorming has been used in order to achieve objective one. Then, the root causes of the NVA and NVA but necessary had been determined using 5 Why's tool. Actions for improvement were proposed and simulated.Finally, the proposed actions for improvement are validated by reduction of total time taken for visual inspection activities. As a result,the total time of visual inspection activities has been reduced for 50% to 70% in which before improvement, total 40% of the total time caused by NVA and NVA but necessary activities.ln conclusion, eliminating NVA and NVA but necessary activities can increase productivity by reduction of process time.